1976
DOI: 10.1080/00332747.1976.11023897
|View full text |Cite
|
Sign up to set email alerts
|

Dream Patterns in Anglo and Chicano Young Adults

Abstract: This study is the conclusion of an exploratory cross-cultural investigation of dream content and organization. Following our report in "Ego Modalities in the Manifest Dreams of Male and Female Chicanos," (Brenneis and Roll, 1975), this paper examines differences in the organization and content of dreams: (1) between Anglo men and women; (2) between Anglo and Chicano men and Anglo and Chicano women; and (3) between Anglos and Chicanos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…Using interviews, projective techniques, and perceptual-cognitive measures, these authors indicated that Mexicans, in contrast to Anglos, tend to value affective rather than cognitive approaches to life. Further evidence for the relatively high interpersonal orientation of Mexican culture is found in the work of Roll & Brenneis (1976). In their cross-cultural investigation of dreams, these au-thors noted that Chicanos in comparison to Anglos reported a greater number of people in their dreams and concluded that "the greater number of characters in the dreams of Chicanos is in keeping with the greater number of people whom Chicanos are likely to think of as important in their lives."…”
Section: Major Errors -A Sins Of Omissionmentioning
confidence: 97%
See 3 more Smart Citations
“…Using interviews, projective techniques, and perceptual-cognitive measures, these authors indicated that Mexicans, in contrast to Anglos, tend to value affective rather than cognitive approaches to life. Further evidence for the relatively high interpersonal orientation of Mexican culture is found in the work of Roll & Brenneis (1976). In their cross-cultural investigation of dreams, these au-thors noted that Chicanos in comparison to Anglos reported a greater number of people in their dreams and concluded that "the greater number of characters in the dreams of Chicanos is in keeping with the greater number of people whom Chicanos are likely to think of as important in their lives."…”
Section: Major Errors -A Sins Of Omissionmentioning
confidence: 97%
“…One characteristic of Anglo culture which is congruent with its focus on an active mode of coping with stress, is a relatively high need for competition and a heavy emphasis on individual achievement. Even in dream reports (Brenneis & Roll, 1976) Anglos are much more likely to organize their experiences so that they are the central figures much more so than Chicanos. In contrast the Chicano culture has placed a higher value on cooperation and collaboration .…”
Section: / Errors In Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Girls typically had more family dreams than boys, and older children dreamt more about peers and school events than younger ones. Earlier research showed that girls dreamt more about family members and home settings than boys (Brenneis & Roll, 1976; Punamäki & Joustie, 1997). My results confirmed, as Kramer (1993) suggested, that age and gender did not affect the mood change, but that the attenuation of negative moods from evening to morning was associated with about what and whom children were dreaming.…”
Section: Discussionmentioning
confidence: 99%